Seismic Fragility Assessment Of Moment-Resisting Concrete Frame With Setback Under Repeated Earthquake - Lau, Ji Wei (Universiti Sains Malaysia, 2017)
This research study is carried out to analyse the seismic behaviour of 10 types six-storey Moment-Resisting Concrete Frames (MRCFs), namely 1 regular frame and 9 setback frames with different building configurations. The setback buildings were mainly emphasised in this analysis because they are becoming increasingly popular in modern multi-storey building construction due to its functional and aesthetic architecture. Incremental Dynamics Analysis(IDA) have been performed on these frames under three sets of repeated ground motion records. Based on the IDA curve, the Life Safety (LS) performance level will be considered as main guideline in order to develop the fragility curve. The maximum inter-story drift percentages at each story level for all the frames and the location of the plastic hinges for each frames can also be determined clearly through IDA. Based on the IDA curve plotted, the mean and standard deviation of the Peak Ground Acceleration (PGA) at drift 1.5% for the frames were determined in order to develop the fragility curve with the life safety performance level. From the results of the fragility curves, the probability of reaching or exceeding the life safety performance state can be determined. The regular frame showed the lowest probability compared to the other frames. As predicted, it has the better seismic performance as compared to the other frames. Among the setback frames, the Model 6T 6 recorded the highest probability of reaching or exceeding the life safety performance level while Model 6T 3 recorded the lowest probability of reaching or exceeding the life safety performance level under any PGA values. Thus, the Model 6T 3 has the best seismic performance while the Model 6T 6 has the poor seismic performance. Thus, it can be known that the building configuration of the frames governs the seismic performance of the building and thus it should be taken into consideration in the building seismic design.